Economic crisis and real critical junctures – on the decay of the political party system of Iceland. Issue 1 (2nd January 2016) - Jonsson, Ivar
Abstract: The political party system of Iceland has since the 1980s developed from decay to crisis. This article explains this development with the real critical conjuncture in 1979–1983 that marked the introduction of the neoliberalist societal regime of Iceland. It argues that despite the crisis of the regime and the political party system, the traditional parties and new political movements such as the Pirates are not likely to create a real critical juncture that will generate post-neoliberalist regime change. Hence, due to structural strains of Iceland as a small economy that suffers from high levels of oligopoly, and because of the persistence of the neoliberalist societal regime of Iceland, it is likely that this regime will generate another financial crisis in the years to come.